2020
DOI: 10.1002/aoc.5594
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of lanthanum (III) and europium (III) 5‐fluorouracil complexes on Caco‐2 cell line

Abstract: Lanthanide complexes are of increasing importance in cancer diagnosis and therapy. In the present study 1:1 and 1:3 solid complexes of La (III)–5‐FU (5‐fluorouracil) were prepared and characterized. In solution, the formation of 1:1 La (III) and Eu (III) complexes enabled the enhancement of 5‐FU's effectiveness. Binding constants of the 1:1 complexes of both metals were estimated using spectrophotometry and HPLC with fluorescence detection methods. The thermodynamic parameters ΔG°, ΔH°and ΔS°were calculated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A La(III)-5-fluorouracil complex (1:1 molar ratio) was synthesized and tested against the Caco-2 cell line (trypan blue exclusion assay). The presence of the La(III) coordination center significantly improved cytotoxicity, compared to 5-fluorouracil [ 128 ]. Molecular docking studies suggested interaction with site II of BSA.…”
Section: Novel Metal Complexes In Cancer Therapymentioning
confidence: 99%
“…A La(III)-5-fluorouracil complex (1:1 molar ratio) was synthesized and tested against the Caco-2 cell line (trypan blue exclusion assay). The presence of the La(III) coordination center significantly improved cytotoxicity, compared to 5-fluorouracil [ 128 ]. Molecular docking studies suggested interaction with site II of BSA.…”
Section: Novel Metal Complexes In Cancer Therapymentioning
confidence: 99%
“…The complexes of rare-earth ions have aroused much interest. Lanthanide ions are the subject of increasing interest in bioinorganic and coordination chemistry 20,21 . Literature studies showed that complexes of lanthanides are associated with several biological properties such as cytotoxic effect and anticancer effect 19,[22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%